2012
DOI: 10.1245/s10434-012-2324-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multiple Apoptotic Mechanism of Shikonin in Human Glioma Cells

Abstract: These studies are the first to show that shikonin-induced apoptosis occurs through multiple pathways in human glioma cells. We conclude that shikonin may be used as a potential chemotherapeutic agent against human glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 20 publications
2
32
0
5
Order By: Relevance
“…36 Furthermore, necroptosis is also activated by shikonin mediated by RIP-1 pathway and oxidative stress in human glioma cell lines, including U87MG cells. 37 In our study, shikonin inhibited cell growth of a panel of 13 EGFRexpressing cancer cell lines with IC 50 values much lower than that of erlotinib, which is a specific inhibitor of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…36 Furthermore, necroptosis is also activated by shikonin mediated by RIP-1 pathway and oxidative stress in human glioma cell lines, including U87MG cells. 37 In our study, shikonin inhibited cell growth of a panel of 13 EGFRexpressing cancer cell lines with IC 50 values much lower than that of erlotinib, which is a specific inhibitor of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having immunomodulatory effects, 9 SHK, as a highly liposoluble naphthoquinone pigment, can inhibit pyruvate kinase M2 activity, 12,13 upregulate p53 activity and downregulate cyclin-dependent protein kinase 4 activity, 14 upregulate BCL2-associated X protein (BAX) and downregulate B-cell lymphoma 2 (BCL2), 6 and inhibit extracellular signal-regulated kinases (ERK) and protein kinase B pathways. 15 All these studies confirm that SHK can induce significant cytotoxicity, while its cytotoxic impacts are not specific to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, SHK is a naturally occurring naphthoquinone with profound inhibitory effects on cancer cell proliferation both in vivo and in vitro. 6,53 Chen et al reported in 2012 that SHK can induce generation of reactive oxygen species, depletion of glutathione, disruption of mitochondrial transmembrane potential, upregulation of p53, cleavage of poly(adenosine diphosphate [ADP]-ribose) polymerase, catalase downregulation, super oxide dismutases (SOD1) upregulation, BCL2 downregulation, and BAX upregulation in U87MG glioma cells. 6 In human glioma cells, SHK-induced necroptosis appears to occur through multiple pathways, while it has also been shown to inhibit the glycolytic path in cancers through inhibiting pyruvate kinase-M2 (PKM2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Здесь же заметим, что способность из-менять трансмембранный потенциал показана для структурного аналога эхинохрома А шиконина (5,8-дигидрокси-3(1´-гидрокси-4-метилпент-3-енил)-1,4-нафтохинон) [52]. Изучение влияния гистохрома на биофизические свойства электро-возбудимых клеток выявило гиперполяризую-щий эффект 2,3,5,6,8-пентагидрокси-7-этил-1,4-нафтохинона [25].…”
Section: +unclassified